The Diversity of the Intensity of Foreign Migration (with the Example of Voivodeships in Poland) - Woźniak, Katarzyna (Studia Oeconomica Posnaniensia, 2017)
The aim of this paper was to identify and assess of the intensity of foreign migration for permanent residence in voivodeships in Poland in the years 2004-2014. The paper consists of three parts. The first part is an introduction to the issue of migration flows. The second part presents absolute and relative measures of the intensity of migration flows. The last part of the paper is an empirical analysis of the intensity of foreign migration in voivodeships in Poland. The analysis hypothesis in the study is the following: voivodeships in Poland characterised by the diversity level of the intensity of foreign migration for permanent residence. The research presents, that voivodeships, which are characterised by the highest intensity of foreign migration for permanent residence were: śląskie, dolnośląskie and opolskie.